2022
DOI: 10.1177/15347354211073066
|View full text |Cite
|
Sign up to set email alerts
|

Preventing Recurrence of Hepatocellular Carcinoma After Curative Hepatectomy With Active Hexose-correlated Compound Derived From Lentinula edodes Mycelia

Abstract: Purpose: Active hexose-correlated compound (AHCC), a standardized extract of cultured Lentinula edodes mycelia, exerts antitumor effects through anti-inflammatory and immune-modulatory functions. Adjuvant therapy for patients with hepatocellular carcinoma (HCC) who have undergone curative hepatectomy has not been established. The purpose of this study was to evaluate the efficacy and safety of AHCC as adjuvant therapy in patients with advanced HCC after curative hepatectomy. Patients and methods: The study des… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 33 publications
(58 reference statements)
0
3
0
Order By: Relevance
“…Therefore, HIRI may be involved in the recurrence of HCC. However, it has been suggested that ECLM may inhibit the recurrence of HCC [ 53 , 54 ]. It may be possible to apply the current investigation of the effect of ECLM on a warm HIRI+PH rat model to human clinical practice by observing the organ-protective effect for hepatectomy requiring frequent PM and the postoperative recurrence rate of HCC after ECLM oral intake.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, HIRI may be involved in the recurrence of HCC. However, it has been suggested that ECLM may inhibit the recurrence of HCC [ 53 , 54 ]. It may be possible to apply the current investigation of the effect of ECLM on a warm HIRI+PH rat model to human clinical practice by observing the organ-protective effect for hepatectomy requiring frequent PM and the postoperative recurrence rate of HCC after ECLM oral intake.…”
Section: Discussionmentioning
confidence: 99%
“…This result for the appearance of the tumor PDX bearing mice administrated by AHCC ® may reflect the clinical findings in humans where AHCC ® improved palliate the medical condition of weight loss and poor physical symptoms caused by the cancer or anti-cancer drug treatment. 25,30) A significant growth inhibition of renal cancer PDX was observed with combination of intraperitoneal and oral administration as AHCC ® in drinking water. In this experiment, AHCC ® administration started i.p.…”
Section: Discussionmentioning
confidence: 99%
“…24) On the other hand, AHCC ® has no such side effects at normal intake levels and is distributed as a functional food. 14) An application of AHCC ® has been reported that AHCC ® is useful for the recuperation of cancer patients or their prognosis, 25) namely reducing the side effects of chemotherapeutic agents during cancer treatment, [26][27][28][29] preventing cancer recurrence, 30) improving the QOL prognosis, and reducing oxidative stress. 31) In this study, we found significant inhibitory effect of AHCC ® on the growth of renal cancer PDX and tendency of the inhibitory effect on the growth of breast cancer (invasive and non-invasive ductal carcinoma) PDX in Super SCID mice.…”
Section: Introductionmentioning
confidence: 99%